Watering Shapes a Robust and Stable Microbial Community under Fusarium Crown Rot Infection - Runlai Xu; Chenghang Du; Yutian Gao; Xiaohan Zhou; Irsa Ejaz; Jieru Guo; Kunhu Chen; Jun Ma; Yinghua Zhang; Zhimin Wang; Zhencai Sun (Agronomy, 2023)
Wheat crown rot, caused by Fusarium pseudograminearum, is an emerging soil-borne fungal disease and causes serious damage in areas where water is scarce. However, the interactions between plant, microbiome, and pathogen under different watering regimes are rarely known. In our study, we designed three watering patterns, including the early-drought (DR1), late-drought (DR2), and well-watered (WAT) patterns, and sampled at heading and grain filling, to investigate the effect of different watering regimes on the microbial community and disease severity. These findings showed that well-watered pattern at grain filling decreased the disease index compared to other patterns, and the bacterial community in the WAT and DR2 at grain filling showed higher alpha diversity (rhizosphere and root) and more stable structures (root). For the microbial network, irrespective of compartments, bacterial networks in the WAT and DR2 were more complex and connected with a higher average degree and clustering coefficient than DR1 at both periods. Furthermore, several potential beneficial microbes as biomarkers were enriched under good water conditions, specifically during the heading of DR2 and grain filling of WAT, including operational taxonomic units (OTUs) affiliated with the taxa of Arenimonas, Sphingomonas, Pseudoxanthomonas, Devosia, Lysobacter, Chitinophagaceae, and Gaiellales in the rhizosphere and root. Overall, the microbiome reshaped by good moisture or avoiding early drought should be emphasized and further used in controlling Fp-caused wheat crown rot.